Measurement of water quality parameters using the spectrophotometry method - Koleva, Radmila; Babunski, Darko; Zaev, Emil; Tuneski, Atanasko; Koleva, Magdalena (University of Niš, Faculty of Mechanical Engineering, Niš, 2024)
Having quality drinking water is a leading factor in maintaining public health, environmental protection, and the promotion of sustainable development in industrial and agricultural needs. Measurement and analysis of chemical parameters in drinking water are crucial for ensuring the safety and quality of water for public health. This research was conducted using the spectrophotometry method including a UVVIS DR 6000 HACH Lange spectrophotometer with a wavelength range of 190 to 1100 nm and a highspeed temperature thermostat HT 200 S. Chemical parameters that are measured in this research are chlorides, nitrates, nitrites, potassium, phosphates, and ammonium. All of them are measured on a different wavelength. Samples were taken from three measuring points, all of which are used as drinking water sources and irrigation in the nearby villages. One measuring point is a thermal spring and the other two springs from the foot of a mountain. The water from all three water sources is considerable drinking water. One sample is taken from Vardar River and its water is considered as non-drinking. The results of all measured parameters will be represented through a table and bar graphic chart.